The effects of financial incentives and rewards towards employee’s commitment in hotel industry / Nik Izzul Islam Azhan Fadzil & Nor Hannan Nasir - Azhan Fadzil, Nik Izzul Islam; Nasir, Nor Hannan (2017)
The purpose of this study is to discuss the effects of financial incentives towards employees’ commitment of hotel industry in Malaysia. Hotel industry has higher turnover rate issue from the employee financial incentives towards the employee’s commitment as it may link with the financial incentives that hotels give to their employees. The study used conceptual study which all the information gathered are based on previous researcher. The study found that promotion and rewards really influences the employee commitment as most of the lower level employee that doesn’t get rewards, they will not show their commitment with their works as the result. The study also found that commitment is usually stronger among senior employees whom already experienced personal success in the organization, and those working with a committed employee group. Plus, the study found that greater perceived person-job fitness was positively influence the organizational commitment. Hence, based on the study if the organization or hotels establish collective plan to reward their employees, it can increase their level of commitment as collective plans will impact positively on employee's loyalty and commitment for that organizations. From the findings, it can be conclude that financial incentives have influences on employee commitment of an organization.